Responsibility for climate change adaptation. (17th July 2019) - Juhola, Sirkku K.
Abstract: As a policy process, climate change adaptation is rapidly advancing. Yet fundamental questions remain unanswered including, who is responsible for planned adaptation and when, who is liable for losses and damages resulting from climate change and how is responsibility distributed in a multilevel governance system? Responsibility can be evaluated in terms of the timing of particular events, the specific societal actors involved and the rules and norms used to attribute responsibility for dealing with those events. Four types of responsibility—care, liability, accountability, and responsiveness for adaptation—are identified, based on empirical studies and examples from the literature. This review demonstrates the need to further explore the normative implications of responsibility and how they should be considered in adaptation governance and policy. This article is categorized under: Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Abstract : Typology of responsibility for climate change.